Pengaruh Pengalaman Kerja dan Disiplin Kerja Terhadap Kinerja Penjualan Jasa Transport pada PT. Wisesa Jaya Santosa - Utami, Ni Komang Dharmi Yudhi (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyse the effect of work experience and work discipline on the performance of employees at PT. Wisesa Jaya Santosa, both simultaneously and partially, as well as to identify the most dominant variables affecting employee performance. This study uses a quantitative approach with saturated sampling techniques on 51 employees. Data were collected through questionnaires, observations, and interviews, then analysed using multiple linear regression with the help of SPSS for Windows. The results showed that work experience and work discipline simultaneously had a significant effect on employee performance with a contribution of 55.4%, while 44.6% was influenced by other variables outside the study. Partially, work experience does not significantly affect employee performance, while work discipline has a significant effect and is the most dominant variable with a contribution of 46.9%. These findings indicate that improvements in employee performance are more influenced by work discipline than work experience.